PEMANFAATAN MICROSOFT INOVATIVE EDUCATION FOLLOW OFFICE 365 PADA MASA PEMBELAJARAN JARAK JAUH (PJJ) DI SMPN 5 PALU - Lamasitudju, Chairunnisa Ar (Faculty of Cultural Studies, Universitas Brawijaya, 2021)
Office 365 is an online learning method that is considered appropriate to be implemented in both partner schools as an additional method to conventional methods. The e-learning method is an electronic learning system that utilizes the internet in its process, allowing teachers to interact with students in online classrooms. SMPN 5 Palu in Central Sulawesi Province is one of the junior high schools strategically located, accessible from three directions with smooth transportation. This school has several strengths, including: highly committed teachers dedicated to improving the quality of graduates, a large number of applicants, high student motivation, and adequate laboratories, including a multimedia laboratory. The teaching methods used by teachers at the partner school have been conventional, such as lectures in the classroom, with no utilization of internet resources in their teaching, as they are unaware of their potential. However, the facilities and infrastructure available to teachers and students are highly supportive, as most teachers and students already have their own laptops, and the school has computer laboratory facilities. Similarly, telecommunications and internet networks now cover almost all areas of Palu City, making it easy to implement online learning. The aim of this training is to enable learning to proceed effectively even under PJJ conditions by adapting to Microsoft Office 365 so that students who are far outside Palu City can still carry out online learning. Assisting teachers in managing online classes, such as uploading materials, creating online practice questions and assigning weights to those questions, creating engaging educational videos from materials, and so on. Microsoft Office 365 is a cloud-based Office application developed by Microsoft that allows users to access various content online via the internet. The development of digital classrooms based on Microsoft 365 has recently been trained to 30 teachers at SMP N 5 Palu.